Sequential therapy with supercharged NK cells with either chemotherapy drug cisplatin or anti-PD-1 antibody decreases the tumor size and significantly enhances the NK function in Hu-BLT mice - Kaur, Kawaljit; Chen, Po-Chun; Ko, Meng-Wei; Mei, Ao; Senjor, Emanuela; Malarkannan, Subramaniam; Kos, Janko; Jewett, Anahid (Frontiers in Immunology, 2023)
We demonstrate that it is possible to eliminate both poorly-differentiated and well-differentiated tumors in-vivo in humanized-BLT mice using supercharged NK (sNK) cells with sequential treatment with either chemotherapeutic drugs or check-point inhibitors. sNK cells were found to be a unique population of activated NK cells with genetic, proteomic, and functional attributes that were very different from primary untreated or IL-2 treated NK cells. NK-supernatant differentiated or well-differentiated oral or pancreatic tumor cell lines are not susceptible to IL-2 activated primary NK cell-mediated cytotoxicity; however, they are greatly killed by the CDDP and paclitaxel in in-vitro assays. Injection of one dose of sNK cells to aggressive oral tumor bearing mice, followed by an injection of CDDP, inhibited tumor growth, and increased IFN-γ secretion as well as NK cell-mediated cytotoxicity substantially in bone marrow, spleen and peripheral blood derived immune cells. Similarly, the use of check point inhibitor anti-PD-1 antibody increased IFN-γ secretion and NK cell-mediated cytotoxicity, and decreased the tumor burden in-vivo in hu-BLT mice when used with sNK cells. The addition of anti-PD-1 or anti-PDL1 to the cocultures of NK cells with MP2, NK-differentiated MP2 or well-differentiated PL-12 pancreatic tumors had an opposing effect on NK and tumor cells depending on the activation of NK cells and differentiation status of the tumor cells, giving us the opportunity to design diagnostic markers to predict which patients will benefit or progress on check point inhibitor treatments. Thus, the ability to target combinatorially clones of tumors with NK cells and chemotherapeutic drugs or NK cells with checkpoint inhibitors at different stages of tumor differentiation may be crucial for successful eradication and cure of cancer.